FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS KEUANGAN PEMERINTAH DAERAH (Survey atas Kompetensi Aparatur, Kualitas Software SIA Penerapan SPI dan Penerapan SAP pada Pemerintah Daerah Kota dan Kabupaten di Provinsi Jawa Barat) - Eko Setyanto; Hamzah Ritchi (Fakultas Ekonomi UNIBBA, 2018)
In improving the financial accountability of Local Government in West Java, in particular has made various efforts such as improving the competence of the apparatus, the quality of accounting information system software, the implementation of internal control system and the implementation of government accounting standards. This study aims to determine the factors that affect the financial accountability of local governments. This research was conducted by using quantitative method. Data were obtained by using questionnaires distributed to 27 Local Government in West Java Province and from LHP BPK RI 2015 and official website of Regional Government. Analysis of this research using multiple linear regression with the help of SPSS IBM Statistics 21 Software, to know the influence of competence of the apparatus, quality of SIA software and SPI application to financial accountability either simultant or partially. The results showed that the factor (competence of apparatus, Quality of Software Accounting Information System, Application of Internal Control) influence to the financial accountability was partially positive and significant, and the relationship of all the independent variables simultaneously with financial accountability are included in the criteria of a very strong relationship.